Pengaruh bauran promosi dan brand awareness terhadap minat beli topi kulit eervoleather - Muhammad Anza Bahrunsyah (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2018)
The purpose of this research is to understand the influence of major promotions and brand awareness towardspurchase intention Eervoleather hat. The research is a quantitative research using the SPSS Statistik 20 program with 111 respondents which are students of General Soedirman Unversity who haveknown promotion activity from Eervoleather by using nonprobability sampling technique and Incidental Sampling. The result of hypothesis analysis show that promotion mix influence significantly to purchase intention; brand awareness influence significantly topurchase intention; and promotion mix and brand awareness have significant effect simultaneously to purchase intention.